The Impact of Variety Seeking, Social Status, Quality and Advertisement Towards Brand Switching in Smartphone Product (A Case Study of BlackBerry User Thas Has Ever Changed Into Another Smartphone Product in Surabaya) - Megan Faustine (iBuss Management, 2015)
When people starts to regard a smartphone as their daily need, BlackBerry, who had ever become a king in Indonesia’s smartphone  industry, suddenly was beaten up. The user starts to change their BlackBerry into another smartphone product. The surprising phenomenon encourages all smartphone industries to have a better performance.This research is conducted to know the impact of variety seeking, social status, quality and advertisement towards brand switching that has been done by BlackBerry user in Surabaya. A total of 103 respondents filled the questionnaires by simple random sampling method.  The data was analyzed using Multiple Linear Regression Analysis. The result shows that variety seeking, social status, quality and advertisement simultaneously impact Brand Switching. When analyzed individually, only variety seeking that has a significant impact towards brand switching decision. Keywords: Brand Switching, BlackBerry, Variety Seeking, Consumer Behavior.